Shedding Light on the Hidden Benefit of Porphyridium cruentum Culture - Davide Liberti; Paola Imbimbo; Enrica Giustino; Luigi D'Elia; Mélanie Silva; Luísa Barreira; Daria Maria Monti (MDPI AG, 2023)
Microalgae can represent a reliable source of natural compounds with different activities. Here, we evaluated the antioxidant and anti-inflammatory activity of sulfated exopolysaccharides (s-EPSs) and phycoerythrin (PE), two molecules naturally produced by the red marine microalga Porphyridium cruentum (CCALA415). In vitro and cell-based assays were performed to assess the biological activities of these compounds. The s-EPSs, owing to the presence of sulfate groups, showed biocompatibility on immortalized eukaryotic cell lines and a high antioxidant activity on cell-based systems. PE showed powerful antioxidant activity both in vitro and on cell-based systems, but purification is mandatory for its safe use. Finally, both molecules showed anti-inflammatory activity comparable to that of ibuprofen and helped tissue regeneration. Thus, the isolated molecules from microalgae represent an excellent source of antioxidants to be used in different fields.